Риск-менеджмент в корпоративном управлении - Угленко, Е. П. (НТУ "ХПИ", 2018)
В статье рассматривается понятийный аппарат категории риск-менеджмента и корпоративного управления в условиях современной экономики. На основании анализа наработок ведущих ученых области проведен теоретический обзор специфики риск-менеджмента в корпоративном управлении предприятия. По итогу работы автором сделан вывод относительно роли эффективного риск-менеджмента в системе корпоративного управления.

The article deals with the conceptual framework of the category of risk management and corporate governance in a modern economy. Based on the analysis of the developments of the leading scientists of the region, a theoretical review of the specifics of risk management in the corporate governance of the enterprise was conducted. Based on the results of the work, the author made a conclusion regarding the role of effective risk management in the corporate governance system.
Risk-management in corporate governance
Keywords: управление предприятием; управление корпоративное; эффективность; стратегия развития; corporate governance; efficiency; strategy